Effects of chitosan and phosphate on quality characteristics and shelf life extension of pork meatballs - Suveena Jantapirak; Supakchon Klongdee; Nipat Limsangouan; Hataichanok Kantrong; Waraporn Prasert (Agriculture and Natural Resources, 2021)
The effects of the chitosan (0%, 0.25%, 0.50%) and phosphate (0%, 0.10%, 0.20%) contents in pork meatballs were studied on the textural properties and their ability to extend product shelf life stored at 4°C for up to 28 d. The physical (texture), and chemical (pH, purge loss, 2-thiobarbituric acid or TBA) properties and microbial growth of pork meatballs were investigated. The results indicated that chitosan could be used as an alternative natural additive to improve both the chemical and physical properties and to extend the shelf life of meatballs. The texture of the meatballs also improved with added chitosan at 0.50% but there was no difference between phosphate added at 0.10% or 0.20%. The TBA value of the meatballs significantly (p < 0.05) decreased with the addition of chitosan, resulting in lower purge loss than for the control. The addition of 0.50% chitosan significantly extended the shelf life by inhibiting microbial growth. At 28 d the total viable count of meatballs with chitosan 0.50% and phosphate 0.20% was 2.51±0.08 log cfu/g while the control sample was 7.70±0.43 log cfu/g. The sensory evaluation determined that the overall acceptance of the chitosan-treated meatballs was higher than for the control.